Optimization of Post-Annealing Treatment Conditions on GaN Layer Grown on m-Plane Sapphire Substrate by Electron Beam Evaporator - Ariff, A.; Zainal,, N.; Hassan,, Z.; Ibrahim, K. (2015)
This paper describes the effect of using different conditions of post-annealing treatment on properties of GaN layer grown on m-plane sapphire by electron beam (e-beam) evaporator. Prior to the annealing, the surface of the grown GaN was found to be smooth with some agglomerations of its grains in a specific direction on the surface. A weak signature of GaN (100) together with Ga203 crystals were also detected. When the annealing was demonstrated at 650°C in N2 ambient, the evidence of Ga203 disappears, especially at 30 minutes of annealing. Annealing in NHa ambient at the same temperature eliminated the GaN (100) crystals but the existence of Ga203 was expected. Further annealing at 950°C in ammonia (NHa) ambient has successfully produced a better non-polar GaN in (100) direction. However, inclusions of GaN (002) and (101) crystals were also detected. Increase in annealing temperature at 980°C and 1100°C caused deteriorations of the structural and optical properties of the GaN layer. From this work, we proposed that the properties of GaN crystalline structure can be controlled by varying the conditions of the post-annealing treatment.